Answer:
A is the answers for the question
Step-by-step explanation:
please mark me as brainlest
Answer:
f(h(-1)) = -1
Step-by-step explanation:
f(x) = (x-4)/3
h(x) = 3x + 4
f(h(-1)) = ?
So first off we need to solve for h(-1):
h(x) = 3x + 4
h(-1) = 3(-1) + 4
h(-1) = 1
Next, we plug this value into the f(x) equation:
f(x) = (x-4)/3
f(1) = (1-4)/3
f(1) = -1
f(h(-1)) may look confusing but it is just f(x) with x being the resulting value for h(-1)
Thus we can say that f(h(-1)) is equal to -1
21.2264 is 21.2 rounded to the nearest tenths; the place after the decimal is there tenths place so in the hundreths place, the number 2 is less than 5 therefore rounding it to 2.
Answer:
Step-by-step explanation:
8x + 12 = 3x + 5x + 12
8x + 12 = 8x + 12
Bringing like terms on one side
8x - 8x = 12 - 12
x = 0